L'economie de l'hydrogene est-elle définitivement enterrée? = Is hydrogen eonomy dead and buried ? - Bento, N. (Revue de l'Energie, 2010)
This article focuses on hydrogen technology and fuel cells, in particular on their mobile applications. The difficulty in introducing hydrogen and fuel cells onto the market stems from the fact that these technologies do not constitute incremental innovation, such as biofuels or hybrid cars, but a real technological breakthrough. Currently, automakers are more active in the promotion of such technology than oil companies. As well as this, manufacturers of fuel cells are trying to accelerate their entry onto the market, in order to limit their period of losses. Finally, public R&D programs continue and public-private partner-ship are being established with a view to financing facilities in california, Japan and Germany.